BODY TEMPERATURE AS A NEW PREDICTOR OF MORTALITY IN HEAD TRAUMA PATIENTS - Nor Hayatunnisa; Rismia Agustina; Oski Illiandri (Universitas Muhammadiyah Ponorogo, 2019)
Head trauma is a neurological emergency that has fairly complex impacts such as physical, cognitive, psychosocial functioning, temporary care. Sixty-five percent of patients with head trauma experience elevated body temperature. Any increase in body temperature by 1 ℃ can have a 5% effect on brain blood flow which lead patients to mortality. Nurses are responsible for patients who experience increased body temperature, especially in providing professional nursing care. The purpose of this research is to know the correlation of body with mortality of head trauma patient at RSUD Ulin Banjarmasin. This research uses non probability sampling method with consecutive sampling technique. The study was conducted in December 2017-January 2018 using an observation sheet. The data analysis shows the p value of 0.003 0.05 which indicates that H0 is rejected means there is a correlation between the body and the mortality of the head trauma patient at Ulin Banjarmasin Hospital. The higher the patient's body temperature the more likely it is to be at risk of mortality.